Analysis of Postpartum Depression Incidence in Gorontalo - Ismail, Yulistian Husin; Soeli, Yuniar Mansye; Wulansari, Ika (Indonesian Journal of Global Health Research, 2024)
The physiological and psychological processes experienced by mothers in the first week after giving birth affect the mother's mental health and increase the risk of postpartum depression. Mothers who have just given birth usually have symptoms of mild depression which will increase 2-5 days after giving birth and subside within 2 weeks. If detection is not done quickly and treatment is done too late, then depression that was initially mild will develop into postpartum depression. This study aimed to describe postpartum depression in postpartum mothers in Gorontalo. This research uses a quantitative descriptive research design. A total sample of 59 respondents was obtained using total sampling techniques. Data analysis used univariate analysis with the EPDS questionnaire instrument. The results of the study showed that the number of postpartum mothers who did not experience postnatal depression was 32 respondents (54.2%), and those who experienced postnatal depression were 27 respondents (45.8%). These results illustrate that the rate of postpartum depression in postpartum mothers in one of the Gorontalo areas is quite high.